2023
DOI: 10.48550/arxiv.2301.05809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Who Should I Trust: AI or Myself? Leveraging Human and AI Correctness Likelihood to Promote Appropriate Trust in AI-Assisted Decision-Making

Abstract: In AI-assisted decision-making, it is critical for human decision-makers to know when to trust AI and when to trust themselves.However, prior studies calibrated human trust only based on AI confidence indicating AI's correctness likelihood (CL) but ignored humans' CL, hindering optimal team decision-making. To mitigate this gap, we proposed to promote humans' appropriate trust based on the CL of both sides at a task-instance level. We first modeled humans' CL by approximating their decision-making models and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(154 reference statements)
0
0
0
Order By: Relevance
“…Optimizing for cooperation with humans is more productive than focusing solely on model performance (Bansal et al, 2021a). Human-AI collaboration research has focused on AI systems explaining their predictions (Ribeiro et al, 2016) or examining the relationship between trust and AI system's accuracy (Rechkemmer and Yin, 2022;Ma et al, 2023). Related to our work, Papenmeier et al (2019); Bansal et al (2021b); Wang and Yin (2022); Papenmeier et al (2022) examined the influence of explanations and found that inaccurate ones act as deceptive experiences which erode trust.…”
Section: Related Workmentioning
confidence: 87%
“…Optimizing for cooperation with humans is more productive than focusing solely on model performance (Bansal et al, 2021a). Human-AI collaboration research has focused on AI systems explaining their predictions (Ribeiro et al, 2016) or examining the relationship between trust and AI system's accuracy (Rechkemmer and Yin, 2022;Ma et al, 2023). Related to our work, Papenmeier et al (2019); Bansal et al (2021b); Wang and Yin (2022); Papenmeier et al (2022) examined the influence of explanations and found that inaccurate ones act as deceptive experiences which erode trust.…”
Section: Related Workmentioning
confidence: 87%